Rita Mendoza and Rick Garcia Wedding at Carmel Church - Watkins, Howard K. (1975)
Christine Watkins, ? Chuck Kahill, Mary Ludy, Christine Burnes, Back: Ruben Lucero, Louis Rodriguez, Christina Russell,? Susan Kahill, Doris Burnes, Elaine Harris